2014
DOI: 10.1073/pnas.1419119111
|View full text |Cite|
|
Sign up to set email alerts
|

The commonly used antimicrobial additive triclosan is a liver tumor promoter

Abstract: Significance Triclosan [5-chloro-2-(2,4-dichlorophenoxy)phenol; TCS] is a broad-spectrum antimicrobial agent that has become one of the most common additives used in consumer products. As a result, TCS has significantly affected the environment and has been frequently detected in human body fluids. Through a long-term feeding study, we found that TCS enhances hepatocyte proliferation, fibrogenesis, and oxidative stress, which, we believe, can be the driving force for developing advanced liver disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
137
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(146 citation statements)
references
References 41 publications
6
137
0
3
Order By: Relevance
“…However, evidence for other mechanisms involving impact on transcription factor activity exists (Stuhlmeier et al, 1999;Tegeder et al, 2001;Veldhoen et al, 2014b). TCS also appears to target transcription factors (Dann and Hontela, 2011;Marlatt et al, 2013;Yueh et al, 2014). The present observation that the gene expression program can be altered at low temperature leading to a noticeable effect at permissive temperature is consistent with modulation of transcription factor status for both TCS and IBF; the associated mechanisms require further investigation.…”
Section: Discussionsupporting
confidence: 71%
“…However, evidence for other mechanisms involving impact on transcription factor activity exists (Stuhlmeier et al, 1999;Tegeder et al, 2001;Veldhoen et al, 2014b). TCS also appears to target transcription factors (Dann and Hontela, 2011;Marlatt et al, 2013;Yueh et al, 2014). The present observation that the gene expression program can be altered at low temperature leading to a noticeable effect at permissive temperature is consistent with modulation of transcription factor status for both TCS and IBF; the associated mechanisms require further investigation.…”
Section: Discussionsupporting
confidence: 71%
“…15 Triclosan can stimulate liver cell proliferation and fibrotic responses by activating CAR and therefore can accelerate hepatocellular carcinoma development, as demonstrated in a tumor promotion study in which triclosan treatment was preceded by administration of DEN in mice. 16 Ligand-elicited CAR activators such as 4-bis- [2-(3, 5-dichloropyridyloxy)] benzene can also promote DEN to induce hepatocarcinogenesis in mice. 17 These lines of evidence have increasingly confirmed that CAR regulators can activate the metabolism of some xenobiotics to induce liver turmorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…One of these dysregulated miRNAs, miR-125b-5p, was differentially expressed in three TCS-exposure groups when compared to the control group. In cancer research, miR-125b is associated with tumor suppressor by down-regulating target oncogene (Yueh et al, 2014). Additionally, several studies have examined miR-125b in relationship to metabolic disorders in mice and humans cell lines (Zhang et al, 2015;Tili et al, 2012).…”
Section: Introductionmentioning
confidence: 99%